Pillbox Organizers are Associated with Improved Adherence to HIV Antiretroviral Therapy and Viral Suppression: a Marginal Structural Model Analysis - Petersen, Maya L.; Wang, Yue; van der Laan, Mark J.; Guzman, David; Riley, Elise; Bangsberg, David R. (Clinical infectious diseases, 2007)
Background. Pillbox organizers are inexpensive and easily used; however, their effect on adherence to antiretroviral medications is unknown. Methods. Data were obtained from an observational cohort of 245 human immunodeficiency virus (HIV)–infected subjects who were observed from 1996 through 2000 in San Francisco, California. Adherence was the primary outcome and was measured using unannounced monthly pill counts. Plasma HIV RNA level was considered as a secondary outcome. Marginal structural models were used to estimate the effect of pillbox organizer use on adherence and viral suppression, adjusting for confounding by CD4+ T cell count, viral load, prior adherence, recreational drug use, demographic characteristics, and current and past treatment. Results. Pillbox organizer use was estimated to improve adherence by 4.1%–4.5% and was associated with a decrease in viral load of 0.34–0.37 log10 copies/mL and a 14.2%–15.7% higher probability of achieving a viral load ⩽400 copies/mL (odds ratio, 1.8–1.9). All effect estimates were statistically significant. Conclusion. Pillbox organizers appear to significantly improve adherence to antiretroviral therapy and to improve virologic suppression. We estimate that pillbox organizers may be associated with a cost of ∼$19,000 per quality-adjusted life-year. Pillbox organizers should be a standard intervention to improve adherence to antiretroviral therapy.